Drugs for Chronic Pain in Children: A Commentary on Clinical Practice and the Absence of Evidence - Marie-Claude Grégoire; G Allen Finley (Pain Research and Management)
Pediatric chronic pain is widespread, under-recognized and undertreated. Best management usually involves a multimodal approach coordinated by a multidisciplinary team. The present commentary specifically discusses common pharmacological approaches to chronic pain in children, identifies gaps in knowledge and suggests several research directions that would benefit future clinical care.